Vibrio cholerae endemic to the lower Rio Grande Delta segregate into urban and rural phylotypes - Daniele Provenzano; Jeffrey W. Turner; Jorge Duran-Gonzalez; David A. Laughlin; Maya Kitaoka; Daniel Unterweger; David Silva; Viviana Trevino; Miguel F. Gonzales; Boris Ermolinsky; Stefan Pukatzki (Scientific Reports)
Abstract The lifestyle of Vibrio cholerae is primarily environmental, yet a chance encounter with a human host can lead to cholera, a potentially lethal form of diarrhea. Strains belonging to O1 and O139 serogroups have pandemic potential, but the contribution of non-O1/non-O139 serovars towards the genesis of cholera remains unclear. Endemic V. cholerae lineages were investigated given several historical accounts describing cholera epidemics and sporadic, contemporary cholera-like outbreaks along the lower Rio Grande Delta (LRGD). Seven isolates were recovered from an urban segment of the Rio Grande and six from a rural segment where the river empties into the Gulf of Mexico. Urban isolates all encode ß-lactamase, and with one exception are phylogenetically closely related, rough (do not express O-antigen), harbor identical plasmids, exhibit a disabled Type VI Secretion System (T6SS), and decreased protease activity. In contrast, rural strains belong to distinct serogroups, are sensitive to ß-lactams, express proteases, and kill Escherichia coli in T6SS competition assays. Genome-scale phylogenetics and multilocus sequence typing indicate that urban and rural isolates belong to distinct and novel phylogroups. These results suggest that an urban niche heavily impacted by anthropogenic pressures and a downstream protected rural niche are inhabited by distinct V. cholerae phylotypes.